Alternative styles turn technique qualitative evaluation to international Spanish junior and pre-junior swimmers: An analysis of error frequency - Sanchez, J. A.; Maanon, R.; Mon, J.; Gonzalez, S.; Arellano, R. (Biomechanics and Medicine in Swimming X, 2006)
This study is a compilation of the analyses developed over four years of the Spanish Junior National Team. The purpose of this study is to determine the frequency of observed errors while front crawl and back crawl turns are performed. 176 junior and pre-junior male and female elite swimmers performed the front crawl turn and 43 performed the back crawl turn. The videorecord was made through an underwater window while a 50 m front crawl or back crawl trial was performed at competitive speed. It was employed an 8mm video cassette recorder. 78% of the group performed an anticipated turn on the longitudinal axis previous to contact with the wall; differences between categories were found. Starting the turn far from the wall and the lack of support for hands during the turn were problems found in over 40% in crawl. The biggest frequency found in backstroke turn was localized in glide and push-off phases (53%).